Pengaruh Gender, Kompensasi dan Lingkungan Kerja Terhadap Loyalitas Karyawan pada CV. Shade Collection Denpasar - I Made Pulawan (Universitas Warmadewa, 2020)
This research was conducted to determine the effect of gender, compensation and work environment simultaneously and partially on employee loyalty of CV. Shade Collection Denpasar and knowing the dominant influencing variables. The number of respondents in this study was 51 people, with the data collection method used, namely the method of observation, interviews and questionnaires. The data analysis technique used is factor analysis and multiple linear regression analysis. The results showed that gender, compensation and work environment simultaneously had a significant effect on employee loyalty of CV. Shade Collection Denpasar. Partially compensation and work environment variables have a significant effect on employee loyalty, while gender has no significant effect on employee loyalty at CV. Shade Collection Denpasar. It is proven that compensation is a variable that has a dominant effect on employee loyalty. Based on the results of this study, it is suggested that CV. Shade Collection Denpasar should pay more attention to the compensation system, especially in terms of providing salaries and overtime pay as well as paying attention to the workplace environment of employees, especially in terms of comfort while doing work.